ANALISIS KUALITAS BAKTERIOLOGIS, KANDUNGAN LOGAM BERAT, SERTA PERILAKU PENGELOLAAN SAMPAH DAN LIMBAH CAIR PADA MASYARAKAT DI SEKITAR SUNGAI AYUNG, DESA KESIMAN PETILAN – KOTA DENPASAR - Bawanti Rahmi, Ni Luh Made Angnidiah Sri Sahanita; Purnama, I Gede Herry (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 3 (2021): Desember 2021DO - 10.24843/ACH.2021.v08.i03.p07, 2022)
ABSTRACT Rivers have an important role in people's lives, from irrigation facilities to being used as raw water sources for clean water. However, the existence of the river is currently threatened by pollution. As one of the longest rivers in Bali Province, the Ayung River also has the potential to be a tourism destination. Therefore, the sustainability of the Ayung River to be maintained. This study aims to determine the quality of river water in the segment that will be used as a new tourism area, in terms of bacteriological and heavy metal content in river sediments, as well as to describe the behavior of people on the banks of the Ayung River in waste and liquid waste management. This study uses a quantitative descriptive design. The results showed that overall, the content of Coliform and Escherecia coli in the three segments of the Ayung River exceeded the normal limit, so that the Ayung River water was polluted in terms of bacteriological and heavy metals. In addition, people's behavior in disposing of waste and household liquid waste around the Ayung River still needs to be improved so as not to pollute the environment and the Ayung River. Therefore, it is necessary to increase the knowledge and awareness of the community in preserving the Ayung River. Keywords: Bacteriology, Heavy Metal, Garbage, Liquid Waste, Ayung River